2004
DOI: 10.1080/09650790400200248
|View full text |Cite
|
Sign up to set email alerts
|

Action research and transformative learning in teaching development

Abstract: The article reports on an action research project, informed by transformative learning theory. Transformative learning involves individuals gaining an awareness of their current habits of mind, and resulting points of views accompanied by a critique of their assumptions and premises, an assessment of alternative views, a decision to negate an old perspective or view in favour of a new one, or to make a synthesis of old and new, resulting in more justified beliefs to guide action. The action research was design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 8 publications
(4 reference statements)
0
51
0
4
Order By: Relevance
“…One way of encouraging more participation in dialogic interaction is to ensure that the learners have content knowledge and evidence on which to draw. This can be achieved through appropriate tasks such as guided reading (Gravett, 2004;Gravett & Peterson, 2002). Confidence in topic and having something to say may mitigate some of the tensions outlined by Tan (2003).…”
mentioning
confidence: 99%
“…One way of encouraging more participation in dialogic interaction is to ensure that the learners have content knowledge and evidence on which to draw. This can be achieved through appropriate tasks such as guided reading (Gravett, 2004;Gravett & Peterson, 2002). Confidence in topic and having something to say may mitigate some of the tensions outlined by Tan (2003).…”
mentioning
confidence: 99%
“…Methods to influence positive collaborative peer interactions coupled to a pedagogical research topic found intriguing to preservice teachers must be central for the development of any research curricula designed for PSTR. Teacher preparation programs have the capability of transforming future teachers professionally and personally to become the quality teachers needed by a diverse population of students today (Gravett, 2004). This transformation of preservice teachers to perceive themselves as professionals who are capable of conducting educational research to make professional and personal decisions with classroom instruction will place the teaching profession as a recognized profession in the United States (Bushaw & Calderon, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Action research is a professional practice and requires an open inquiring mind, with the learning needs of students considered to be the most imperative part of instructional design (Jaruszewicz, 2006;Stringer, Christensen, & Baldwin, 2010). K-12 education systems can be transformed into proactive, professional learning environments using action research as the means for all instructional decision making (Batagiannis, 2011;Good, 2009;Gravett, 2004). K-12 schools are experiencing this transformation now in various areas like science instruction and special education instruction; teachers today are finding the teacher/researcher mantle of using data for decision making fundamental to success for teaching professionals (Lebak & Tinsley, 2010;Roach, Kurz & Elliott, 2015).…”
Section: Action Research In the Classroommentioning
confidence: 99%
“…Professional development opportunities do facilitate the perspective transformation. (King, 2002) The use of transformative learning in educational setting carries higher education as its example (Barlas, 2001;Glisczinski, 2007;Gravett, 2004). It also includes cooperate human resources development (Hsiao & Chang, 2011), academic committees (Kokkos, 2010), community education (Silverman, 2004) and professional development for teachers (Griswold, 2007;McQuiggan, 2006).…”
Section: Introductionmentioning
confidence: 99%